LOAD LENGTH CONCENTRATION STARS IN CHAINS AND DEVICES - Vitaliy Kovalevsky, Shorahmat Shoobidov, Umid Mamasobirov (International Journal of Advanced Science and Technology, 2020)
This article is devoted to calculating the distribution of the load concentration along the length of the sprocket teeth in a chain transmission. The main parameters of the contact between the tooth of an asterisk and roller (sleeve) are analyzed - the maximum load on the surface of the contact, the width and length of the contact area. The calculated dependences on the distribution of the load concentration along the length of the sprocket teeth in chain transmissions are given. An analysis of the calculation formulas shows that the flexibility of the transmission elements (shafts, chains, head joint) favorably affects the working conditions of the gearing of chain gears.